Cascade emission in electron beam ion trap plasma of W25+ ion. (July 2015) - Jonauskas, V.; Pütterich, T.; Kučas, S.; Masys, Š.; Kynienė, A.; Gaigalas, G.; Kisielius, R.; Radžiūtė, L.; Rynkun, P.; Merkelis, G.
Abstract: Spectra of the W 25 + ion are studied using the collisional-radiative model (CRM) with an ensuing cascade emission. It is determined that the cascade emission boosts intensities only of a few lines in the 10–30 nm range. The cascade emission is responsible for the disappearance of structure of lines at about 6 nm in the electron beam ion trap plasma. Emission band at 4.5–5.3  nm is also affected by the cascade emission. The strongest lines in the CRM spectrum correspond to 4 d 9 4 f 4 → 4 f 3 transitions, while 4 f 2 5 d → 4 f 3 transitions arise after the cascade emission is taken into account. Abstract : Highlights: Spectra of the W 25 + ion are calculated using the collisional-radiative model. Influence of cascade emission on the formation of lines is studied. Cascade emission boosts intensities only of a few lines in the 10–30 nm range. Emission band at 4.5–5.3 nm is affected by the cascade emission. Time-integrated study of the line intensities is presented.